Fishy Pleasures: Unsettling Fish Hatching and Fish Catching on Pacific Frontiers - Woelfle-Erskine, Cleo (Imaginations)

(untitled) (York University, 2019)
In debates over Puget Sound salmon recovery, the Wild Steelhead Federation, a settler sportfishing advocate, argues that hatchery-raised steelhead lack fighting spirit, and figures them as unnatural. The Northwest Indian Fisheries Commission and its member tribes operate hatcheries as strategy for maintaining fish runs until degraded habitats can be restored, and figure hatcheries as one of many sites of making relations. Although the genetic science mobilized on all sides of this debate is fairly new, settler discourses that, on the one hand, blame tribal harvest for salmon decline and, on the other hand, construe sportfishing as central to settler family-making and masculinities, have roots going back to the notion of the frontier itself. As a slantwise intervention in this debate, I consider sportfishing as a site and strategy for making settler sexualities, by examining visual archives that document historical practices of sportfishing and the technologies on which contemporary salmon and trout sportfishing depends: the reservoir, the fish hatchery, and the fishing pole. Tracing arguments about Nature and settler masculinities back to the origins of fish culture in hatcheries through the writing of George Perkins Marsh, I argue labeling either normative settler sexualities and gender relations or the flooded spawning grounds beneath reservoirs as unnatural threatens co-constituted settler sexualities and reworkings of “natural” landscapes.